Scientific School of Volga State Technological University in Economics and Finance: Formation, Development, Prospects - O. A. Mironova (Учёт. Анализ. Аудит)
The article deals with the issues of formation and development of the scientific school of the Volga Region State Technological University — Volgatech (VSTU) in economics and finance, the basic provisions of which are recognised as: accounting and analytical, control support of management systems and economic security; concepts of tax administration and tax security; methodology of economic analysis; monitoring and systems of its information support. The adaptation of the scientific school to the conditions of reality, in which the Russian economy is developing, is based on the concentration of attention on the nodal issues of national interests, economic development and economic security, as well as tax and budgetary policy, which have a significant impact on the formation of the information system for management and ensuring sustainable and safe development of economic entities. The authors of the study also paid attention to the stages of formation and historical development of the scientific school on the basis of the Volga Region State Technological University, its relationship with the scientific community, key areas of work that determine its further development.